Gender-wise Distribution of Cardiovascular Risk and Its Correlation with Dietary Intake, Physical Activity, and Perceived Stress: A Cross-sectional Study - Ambrin Zenab; Sudhanshu Kacker; Neha Saboo; Munesh Kumar (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Cardiovascular Diseases (CVDs) are a group of disorders affecting the heart and blood vessels, including Coronary Heart Disease (CHD), cerebrovascular disease, rheumatic heart disease, peripheral artery disease, congenital heart disease, and pulmonary embolism. CVDs contribute to approximately 17.9 million deaths worldwide each year. Risk factors for CVDs can be classified as non modifiable (such as age, gender, ethnicity, and family history) and modifiable (such as obesity, dyslipidaemia, diabetes, hypertension, stress, poor diet, and physical inactivity). Men are more susceptible to CVDs than women. The QRISK3 risk score is an algorithm used to predict an individual’s 10 year risk of developing CVDs. Aim: To assess the distribution of CVD risk among men and women aged 30-70 years using the QRISK3 risk score and its correlation with dietary intake, physical activity, and perceived stress. Materials and Methods: A cross-sectional study was conducted at the Department of Physiology at RUHS-CMS and Associated Hospitals in Jaipur, Rajasthan, India. The study duration was six months, from July 2022 to December 2022. A total of 220 subjects, aged 30-70 years, of both sexes were recruited from the Outpatient Department (OPD) of Medicine, based on inclusion and exclusion criteria. The QRISK3 web calculator was used to calculate the CVD risk, which was then correlated with the Food Frequency Questionnaire (FFQ), Perceived Stress Scale (PSS), and Global Physical Activity Questionnaire (GPAQ). Statistical analysis was performed using the Chi-square test for qualitative analysis, and Pearson’s correlation analysis was used to assess correlations. Results: The mean age of the study participants (males) was 42.75±10.86 years and (females) was 42.82±10.85 years. A total of 220 participants (123 males and 97 females) aged between 30-70 years were included in the study. Among the males, 90 (73.17%) had low CVD risk, 15 (12.19%) had moderate risk, and 18 (14.63%) had high risk. Among the females, 83 (85.57%) had low risk, 9 (9.28%) had moderate risk, and 5 (5.15%) had high risk. There was a significant association between the QRISK3 risk score and gender (χ2 =6.14, df=218, p=0.04). Males showed a stronger association with the QRISK3 risk score compared to females within different age groups. Significant positive correlations were observed between the QRISK3 score and FFQ (r=0.28) and PSS (0.42). Additionally, a significant negative correlation was found between the QRISK3 score and GPAQ (-0.24). Conclusion: The QRISK3 score calculator was found to be useful in assessing the 10-year risk of developing CVDs in males and females across different age groups. The association between CVD risk and various scores suggests that perceived stress is strongly correlated with CVD risk.